2012
DOI: 10.1016/j.ijge.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The Unmet Activities of Daily Living (ADL) Needs of Dependent Elders and their Related Factors: An Approach from Both an Individual- and Area-Level Perspective

Abstract: s u m m a r yBackground: The unmet activities of daily living (ADL) needs often lead to negative consequences in dependent elders. This study examines disabled elders' unmet ADL needs and the factors associated to those unmet needs. Methods: Data from a representative sample from Taiwan of 6820 elders and family caregiver dyads were analyzed, using hierarchical linear modeling to identify the individual-and area-level factors. Standardized measures were administered through face-to-face interview. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 15 publications
8
31
2
Order By: Relevance
“…Moreover, some indicated that the prevalence of unmet needs among elderly people who required assistance in any of the six tasks for more than 3 months in China was even higher than that of this study, reaching 61.4% [7]. Furthermore, older adults in rural areas had a higher rate of unmet needs than their urban counterparts, which is in line with other studies [16,24]. Despite the different measures of unmet LTC needs, we can see that China, especially rural areas of China, faces great challenges in terms of unmet LTC needs among older people.…”
Section: Prevalence Of Unmet Ltc Needssupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, some indicated that the prevalence of unmet needs among elderly people who required assistance in any of the six tasks for more than 3 months in China was even higher than that of this study, reaching 61.4% [7]. Furthermore, older adults in rural areas had a higher rate of unmet needs than their urban counterparts, which is in line with other studies [16,24]. Despite the different measures of unmet LTC needs, we can see that China, especially rural areas of China, faces great challenges in terms of unmet LTC needs among older people.…”
Section: Prevalence Of Unmet Ltc Needssupporting
confidence: 88%
“…However, some studies have indicated this proportion may have been underestimated because respondents who received assistance were not asked whether that help was adequate or sufficient in the National Long-Term Care Survey in the USA [9,23]. Another study reported that the prevalence of BADL disability among elderly people aged 65 and over in Brazil was 16.0% and that 47.0% of those people with disabilities had their needs met, while only 10.3% did not [13]. In that study, unmet needs were defined as the presence of at least one unavailable need for BADLs.…”
Section: Prevalence Of Unmet Ltc Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, quite a few studies have shown that social function among Chinese elderly people is closely related to social networks (not only those of family and friends, but also those of formal and informal participation in community groups and organisation) and to social attachments (in terms of social trust, mutual benefit, reciprocity and solidarity, etc.) within the community (Chiu & Yu, 2001;Jiang, 2009;Lei, 2001;Liu, Chang, & Huang, 2012;Wang, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Having an in‐home or other family carer is protective; however, carer characteristics such as older age [13], psychological morbidity [12,13], lower psychological quality of life (QOL) [11] and carer burden [14,15] also predict nursing home admission. Unmet care needs in community‐dwelling older people are associated with other adverse outcomes such as weight loss, dehydration, falls, burns and discomfort [16], greater psychological distress and elevated carer stress [17], hospital admissions [6,15], and mortality [15]. Home care delays nursing home admission [18,19]; this may be by reducing unmet care needs and carer burden [20,21].…”
Section: Introductionmentioning
confidence: 99%